Design and Implementation of a Sociocultural Didactic Sequence for the Preservation of Traditional Vallenato Music in Secondary Education: A Case Study in Cesar - Pizarro, Alcides Caleb Manotas; Urieles, Edelmira Pizarro; Guevara, Jhenifer Rincón; Munoz, Martha Esther Guerra; Quiroz, Carmen Beatriz Araujo (Journal of Posthumanism, 2025)
This article presents the results of a qualitative research oriented to the design and implementation of a didactic sequence with a socio-cultural approach for the preservation of traditional vallenata music in secondary education, in an institution of the department of Cesar, Colombia. The study responds to the need to strengthen cultural identity and the intergenerational transmission of intangible heritage in a context marked by globalization and the loss of local cultural references. A case study methodology was used, integrating interviews, participant observation, focus groups and documentary analysis. The results show a significant increase in the students' interest, knowledge and appreciation of traditional vallenato, as well as improvements in school coexistence and critical thinking. The proposal demonstrates the relevance of contextualized pedagogical strategies for the safeguarding of musical heritage and the formation of intercultural citizenship.